Outcome of CPAP Titration for Moderate-to-Severe OSA Under Drug-Induced Sleep Endoscopy: A Randomized Controlled Crossover Trial - Wang, Tsai-Yu; Huang, Yu-Chen; Lin, Ting-Yu; Ni, Yung-Lun; Lo, Yu-Lun (Frontiers in Neurology, 2022)
ABSTRACT Background: The titration pressure of continuous positive airway pressure (CPAP) is important for patients with obstructive sleep apnea (OSA). This study aimed to understand the difference between drug-induced sleep endoscopy (DISE)-guided CPAP titration and conventional sleep center (CSC) CPAP titration on OSA patients. Methods: In this randomized controlled single-blinded crossover trial, we compared the effects of 1-month CPAP treatment in OSA patients with either DISE-guided CPAP titration or CSC CPAP titration. Twenty-four OSA patients were recruited for this study. All patients underwent polysomnography, DISE-guided CPAP titration, and accommodation. Initially, patients were randomly assigned to receive either DISE-guided CPAP titration or CSC CPAP treatment for the first month. They then switched to the other treatment for the second month. Epworth sleepiness scale (ESS) was recorded at baseline, 1 month, and 2 months. Results: The upper limited pressure from DISE-guided titration or CSC CPAP titration had no significant differences (13.9 ± 0.7 cm H2O vs 13.5 ± 0.5 cm H2O; P = 0.92). Residual apnea-hypopnea index (AHI) and compliance were also not significantly different between the groups. The ESS significantly improved from baseline to 1-month CPAP treatment in both groups. Both epiglottis (anterior-posterior collapse) and tongue base collapse were significantly associated with 95% CPAP pressure (P = 0.031 and 0.038). After multivariate regression analyses, epiglottis (anterior-posterior collapse) was the independent factor for 95% CPAP pressure. For the safety concern of DISE, the incidence of bradycardia is 58.3%. Even though the high incidence of bradycardia, all patients who experienced bradycardia recovered under proper management. Conclusion: Both modalities are comparable in terms of establishing the pressure settings required to treat patients. Further large-scale study is warranted to confirm the results.